Crash responses under multiple impacts and residual properties of CFRP and aluminum tubes. (15th June 2018) - Liu, Qiang; Shen, Hao; Wu, Yinghan; Xia, Zhencong; Fang, Jianguang; Li, Qing
Abstract: This study aimed to explore the impact responses and residual properties of thin-walled carbon fiber reinforced plastics (CFRP) tubes and aluminum (Al) tubes subjected to multiple axial impacts. Five repeated impacts with the same impact energy were first conducted to evaluate the effect of repeated impact number, and then the crushing tests were performed to explore the post-impact residual behavior. Regardless of number of repeated impacts, the progressive end crushing modes for the CFRP tubes and stable progressive folding mode for aluminum tubes were identified under repeated dynamic impacts. The CFRP tubes exhibited the highest specific energy absorption (SEA) under the 1st impact, then the similar SEA values in the other four subsequent impacts; whereas the SEA of aluminum tubes fluctuated with the repeated impact numbers which were related to formation of different folds. The quasi-static crushing tests revealed that the residual SEAs of the CFRP tubes and aluminum tubes were not much influenced by the impact number, only within a difference of 5% under the 5 repetitive impacts conducted. It was demonstrated that the CFRP tubes had much better performance in energy absorption capability in comparison with the aluminum tubes in terms of repeated impacts and residual crushing tests.